Poetas no topo - André Pires Guerra Aguiar (2021)
Contemporary poetry has been very much discussed in the theoretical field, although literary theoretical researchers have had quite difficulty in conceptualizing it. Pixação itself has not been presented anymore in public spaces, but in oficial artistic locations, such as museums and galleries, and it has established dialogue with publicity, design, fashion, art and even cinema, besides literature. Therefore, the present dissertation approaches pixação to what theoretical researchers call “literature in the expanded field”, “literature outside itself”, “apoetry”, “post autonomous literature”, and many other forms of calling these contemporary writing manifestations. This relation has been established using the speeches of the people who practise it and using the lecture of the practice relating to performance. Hence, pixação appears as a deeply rich universe, which goes beyond the stigmatized weight that it usually carries. Concluding, the present dissertation demonstrates the way that contemporary poetry approaches performance and its language, according to many similar characteristics between these practices.